2009
DOI: 10.1586/ern.09.70
|View full text |Cite
|
Sign up to set email alerts
|

Targeting eNOS and beyond: emerging heterogeneity of the role of endothelial Rho proteins in stroke protection

Abstract: SummaryCurrently available modalities for the treatment of acute ischemic stroke are aimed to preserve or augment cerebral blood flow (CBF). Experimental evidence suggests that statins, which show 25-30% reduction of stroke incidence in clinical trials, confer stroke protection by upregulation of eNOS and increasing CBF. The upregulation of eNOS by statins is mediated by inhibition of small GTPbinding protein RhoA. Our recent study uncovered a unique role for a Rho-family member Rac1 in stroke protection. Rac1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 154 publications
0
25
0
Order By: Relevance
“…In addition to the BBB, brain ECs also regulate cerebral blood flow and vasoreactivity (33), as well as cerebrovascular inflammation and thrombosis (9). Although the current work underscores the importance of KLF2 in BBB regulation, we recognize that additional mechanisms may be operative in the observed stroke phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the BBB, brain ECs also regulate cerebral blood flow and vasoreactivity (33), as well as cerebrovascular inflammation and thrombosis (9). Although the current work underscores the importance of KLF2 in BBB regulation, we recognize that additional mechanisms may be operative in the observed stroke phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, nitric oxide is also an important second messenger especially in endothelial and neuronal cells. Indeed, increase in NO production through the stimulation of eNOS activity has been reported to protect against stroke through a wide range of cellular effects, including vasodilation, antithrombotic, anti-inflammatory and anti-proliferative activities [41]. One of the striking clinical symptoms in MELAS is the occurrence of stroke-like episodes, which is supposed to be linked to the NO metabolism [11].…”
Section: Discussionmentioning
confidence: 99%
“…37,38 It is also reported that the modulation of eNOS mRNA stability plays an important role in eNOS regulation, especially in response to pathological stimuli, including oxidized LDL and cytokine tumor necrosis factor-␣. 39 Importantly, eNOS mRNA stability was found to be regulated by statins, 40 which are widely used in clinical cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%